“Polite but Firm”: Critical Discourse Analysis of Kang Dedi Mulyadi’s Politeness Strategy in Responding to Public Criticism - Santoso, Dwi (Journal of Linguistica, 2025)
This article applies Fairclough’s Critical Discourse Analysis (CDA) to examine how West Java Governor Kang Dedi Mulyadi (KDM) responds to public criticism through the strategic use of language. Analyzing ten statements from social media and online news outlets (2024–2025), the study finds that KDM employs mitigating, persuasive, and assertive politeness strategies to maintain authority while building public trust. These strategies reflect a model of ethical and communicative leadership that transforms criticism into constructive dialogue. Rather than silencing dissent, KDM uses language to manage tension, clarify responsibilities, and engage the public in meaningful ways. The study highlights how discourse can function as a tool for both power negotiation and reputation building in Indonesia’s digital political sphere. It also demonstrates that politeness in political communication is not just etiquette, but a strategic means of navigating public discourse. This approach offers valuable insights into how leaders can maintain legitimacy and credibility in the social media age.